A national physician survey of diagnostic error in paediatrics - Perrem, L; Fanshawe, T; Sharif, F; Plüddemann, A; O'Neill, M (Springer Berlin Heidelberg, 2016)
This cross-sectional survey explored paediatric physician perspectives regarding diagnostic errors. All paediatric consultants and specialist registrars in Ireland were invited to participate in this anonymous online survey. The response rate for the study was 54% (n=127). Respondents had a median of nine years clinical experience (IQR 4-20 years). A diagnostic error was reported at least monthly by 19 (15.0%) respondents. Consultants reported significantly less diagnostic errors compared to trainees (p value = 0.01). Cognitive error was the top ranked contributing factor to diagnostic error, with incomplete history and examination considered to be the principal cognitive error. Seeking a second opinion and close follow-up of patients to ensure that the diagnosis is correct were the highest ranked clinician-based solutions to diagnostic error. Inadequate staffing levels and excessive workload were the most highly ranked system-related and situational factors. Increased access to and availability of consultants and experts was the most highly ranked system-based solution to diagnostic error. Conclusions: We found a low level of self-perceived diagnostic error in an experienced group of paediatricians, at variance with the literature and warranting further clarification. The results identify perceptions on the major cognitive, system-related and situational factors contributing to diagnostic error and also key preventative strategies.